2020
DOI: 10.3389/fmicb.2020.02100
|View full text |Cite
|
Sign up to set email alerts
|

Development of HiBiT-Tagged Recombinant Infectious Bronchitis Coronavirus for Efficient in vitro and in vivo Viral Quantification

Abstract: Coronaviruses (CoVs) are enveloped (+) ssRNA viruses of veterinary and medical importance. Because recombinant CoVs with reporter proteins fused with viral proteins are usually non-viable or unstable, a small and quantifiable epitope tag would be beneficial to CoV research. In this study, we integrated the NanoLuc Binary Technology to the reverse genetics of infectious bronchitis virus (IBV), a prototypic gammacoronavirus. The 11-amino-acid HiBiT tag was inserted to the spike (S) or membrane (M) protein, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Here, we found that the 11-amino acid HiBiT tags used to monitor VLP production and entry can be appended to different structural proteins of SARS-CoV2, as demonstrated by the VLP-cell entry assays ( Figure 6 ). This advances the NanoBiT technology to SARS-CoV2, building from a recent report that has shown the utility of HiBiT tags on spike or membrane protein of infectious bronchitis coronavirus [ 57 ]. Using sensitive NanoBiT technology, the system isolates virus-cell entry and can thereby recognize the receptors and proteases operating as coronavirus-cell susceptibility factors ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that the 11-amino acid HiBiT tags used to monitor VLP production and entry can be appended to different structural proteins of SARS-CoV2, as demonstrated by the VLP-cell entry assays ( Figure 6 ). This advances the NanoBiT technology to SARS-CoV2, building from a recent report that has shown the utility of HiBiT tags on spike or membrane protein of infectious bronchitis coronavirus [ 57 ]. Using sensitive NanoBiT technology, the system isolates virus-cell entry and can thereby recognize the receptors and proteases operating as coronavirus-cell susceptibility factors ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the effect of Retro-2.2 on F trafficking, we then quantified the presence of F at the plasma membrane. To overcome the potential bias linked to cell fusion and of immunostaining, we generated an F surrogate which consisted in the insertion in place of the F ectodomain of the sequences of the mCherry and of the HiBit peptide, an 11-amino-acid-long optimized peptide of the split Nano Luciferase ( Figure 3 A) [ 40 , 41 , 42 ]. The plasmid encoding this chimeric protein was transfected in HEp-2 cells which were incubated for 24 h in the absence or presence of 2 µM Retro-2.2.…”
Section: Resultsmentioning
confidence: 99%
“…Recovery of rIBV-Beau-KC(S1) from the cloned cDNA was performed according to a protocol that was successfully used for the recovery of a HiBiT-tagged recombinant IBV (Liang et al, 2020). Vero cells were electroporated with the in vitro transcribed full-length and N transcripts and cultured up to 96 h post-electroporation.…”
Section: Resultsmentioning
confidence: 99%